Robust finite-time stabilization of nonlinear systems with multiple delays in states and controls - P. Niamsup (2018)
This paper is concerned with the problem of robust finite-time stabilization for a class of nonlinear systems with multiple delays in state and control and disturbance. The disturbance under consideration is norm bounded. By using Lyapunov function method and LMI techniques, two types of feedback controllers, one being memory and the other memoryless, are constructed. The derived conditions are formulated in terms of linear matrix inequalities (LMIs). Finally, two numerical examples are provided to show the effectiveness of the proposed results.